STRATEGI MANAJEMEN RISIKO PADA LEMBAGA KEUANGAN SYARIAH DALAM MENGHADAPI VOLATILITAS PASAR: TELAAH TEORI MANAJEMEN RISIKO DAN EKONOMI ISLAM - Ahmad Riyadi; Mubarik Mubarik (Adisam Publisher, 2025)
This study discusses risk management strategies in Islamic financial institutions in facing market volatility by examining the integration between modern risk management theory and Islamic economic principles. Amidst the dynamics of a global economy full of uncertainty, Islamic financial institutions require a risk management approach that is capable of maintaining operational stability while complying with Shariah values. This study uses a literature review method by collecting and analysing various scientific literature to produce a conceptual mapping of the application of prudential principles based on maqashid al-shariah. The results show that risk management in the Islamic financial system must be based on the concepts of risk sharing, avoidance of riba, gharar, and maysir, as well as the application of sharia-based governance. The integration of conventional risk management theory with Islamic values has given rise to a new paradigm that is not only oriented towards asset protection, but also towards the creation of social justice and economic sustainability for the people. Thus, sharia risk management can become a key pillar in building an ethical, stable financial system that is resilient to global market fluctuations.